Diagnosis and management of pancreatic cystic neoplasms. Issue 3 (1st March 2019) - Keegan, Mathew James; Paranandi, Bharat
Abstract : This review outlines the current classification of pancreatic cystic lesions, with a particular emphasis on pancreatic cystic neoplasms (PCNs). It will describe the diagnostic approach to PCNs, with reference to clinicopathological features, cross-sectional radiology and endoscopic ultrasound. This review will conclude with an evidence-based discussion of the management of PCNs focused on recent clinical guidelines.